VOLCANIC GASES, BLACK SMOKERS, AND THE GREAT OXIDATION EVENT - Holland H.D. (My University, 2002)
This paper proposes that gradual changes in the composition of volatiles that have been added to the atmosphere-ocean system are responsible for the Great Oxidation Event (G.O.E.) ca. 2.3 Ga. Before ca. 2.3 Ga, the composition of these volatiles was probably such that 20% of the carbon gases could be reduced to organic matter and all of the sulfur gases could be reduced to pyrite. Since 2.3 Ga, the composition of these volatiles has been such that 20% of the carbon gases could be reduced to organic matter, but only a fraction of the sulfur gases could be reduced to pyrite. This change led to the oxygenation of the atmosphere and to a large increase in the SO4−2 concentration of seawater. A considerable body of observational data supports these proposals.